THE ROLE OF MAGNETIC METHODS IN THE STUDY OF AREAS OF THE TIGHT OIL AND GAS: INTRODUCTION - Menshov О. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
One of the possible ways to increase the production of hydrocarbon raw materials of Ukraine origin is the attraction of the sources of tight oil and gas reservoirs. The relevance of this direction for Ukraine is confirmed by a number of decisions of the NSDC, Cabinet of Ministers of Ukraine, and priority areas of the Horizon Europe program. Magnetic methods for studying the near surface geological section and soil of hydrocarbon fields is a fast, energy-saving and cheap technology. The technique is the same for the unconventional or classical type, thus the genesis of the deposit is not important. The high information content of magnetometry in oil and gas exploration is based on the assumption of hydrocarbon migration (microseepage). This fact is confirmed by seismic, radioactive, and geochemical methods. The case study from hydrocarbon deposit at the area of Balabanovka, Bogodukhovsky district, Kharkov region, is considered. At this stage, we analyze only a part of the reconnaissance materials. The soil is deep medium-humus chernozems. We collected 29 samples at the areas of hydrocarbon influence: well Nedilna-1 (productive) and Nedilna-2 (nonproductive). In laboratory conditions, the mass-specific magnetic susceptibility (χ, MS) was measured with kappabridge KLY (Agico, Czech Republic), and its frequency dependence χfd by the MS2B (Bartington, UK). The content of hexane in soil was determined at the laboratory of the Institute of Geological Sciences of the NAS of Ukraine. The maps were built using the IDW interpolation method in the ArcGIS environment., There are areas of overlap of increased MS values and decreased values of the hexane content in the western part. The increased MS values were registered in the zone of the productive well Nedilna-1. The average MS values were detected near the non-productive well Nedilna-2. The maximum values of the hexane content were registered near both wells. The correlation analysis of MS and the content of hexane in soils showed the presence of an average negative relationship: R= -0.4 (n=28, p<0.05, r≥0.3233). Hydrocarbons and their oxidation products have significant migratory mobility, which leads to the formation of autogenous magnetic minerals from the deposit zone to the soil. The result is the formation of anomalous values of magnetic susceptibility, remanent magnetization, and other magnetic parameters.